Analysis Of Individual Taxpayer's Perception Of Tax Evasion - Sindik Widati; Maulina Dyah Permatasari; Anna Fiana (DPPM Universitas Pelita Bangsa, 2023)
This study aims to determine the effect of the taxation system, tax knowledge and self-assessment system on tax evasion in the South Cikarang KPP case study. In this study the independent variables used were the influence of the tax system, tax knowledge and the self-assessment system, while the dependent variable was tax evasion. This study uses a quantitative approach, using primary data through questionnaires. The population in this study are taxpayers who are registered at South Cikarang KPP. The testing technique of this research consists of instrument test, classical assumption test and multiple linear regression test. The test results show that the tax system has no and significant effect on tax evasion, the understanding factor of taxation has no significant effect on tax evasion, the Self Assessment system factor has a significant effect on tax evasion